2016
DOI: 10.1021/acsami.6b01523
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Encapsulated AuNR@Ag/Au Nanosphere SERS Tags with Environmental Stimulus Responsive Signal Property

Abstract: Surface-enhanced Raman scattering (SERS) tags draw much attention due to the ultrasensitivity and multiplex labeling capability. Recently, a new kind of SERS tags was rationally designed by encapsulating metal nanoparticles with phospholipid bilayers, showing great potential in theranostics. The lipid bilayer coating confers biocompatibility and versatility to changing surface chemistry of the tag; however, its "soft" feature may influence SERS signal stability, which is rarely investigated. Herein, we prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…Currently photothermal therapy is a widely studied therapy. The reagents commonly used in photothermal therapy include precious metal nanoparticles, [36][37][38][39][40] small molecule reagents, [41][42][43] carbon based nanomaterials, [44][45][46] in vivo photothermal effect is the most direct verication method for evaluating nanoparticles for photothermal therapy, so we veried the photothermal treatment of FePd@M nanoparticles in vivo. We randomly divided BALB/c nude mice bearing Huh-7 liver tumor into four groups.…”
Section: In Vivo Photothermal Therapymentioning
confidence: 99%
“…Currently photothermal therapy is a widely studied therapy. The reagents commonly used in photothermal therapy include precious metal nanoparticles, [36][37][38][39][40] small molecule reagents, [41][42][43] carbon based nanomaterials, [44][45][46] in vivo photothermal effect is the most direct verication method for evaluating nanoparticles for photothermal therapy, so we veried the photothermal treatment of FePd@M nanoparticles in vivo. We randomly divided BALB/c nude mice bearing Huh-7 liver tumor into four groups.…”
Section: In Vivo Photothermal Therapymentioning
confidence: 99%
“…Thus the hydrodynamic diameter gives us information of the core along with any coating material and the solvent layer attached or adsorbed to the particle as it moves under the influence of Brownian motion. While estimating size by TEM, this hydration layer is not present hence, we get information only about the core and coating material (Peng et al, 2010;Su et al, 2016). Moreover, obtained results from zetasizer have a good correlation with the results of TEM (Peng et al, 2010;Bhaumik et al, 2015;Su et al, 2016;Thakur et al, 2017).…”
Section: Discussionmentioning
confidence: 78%
“…While estimating size by TEM, this hydration layer is not present hence, we get information only about the core and coating material (Peng et al, 2010;Su et al, 2016). Moreover, obtained results from zetasizer have a good correlation with the results of TEM (Peng et al, 2010;Bhaumik et al, 2015;Su et al, 2016;Thakur et al, 2017). FTIR studies showed that the drugs and their nanoparticles have integral properties of each component and the drugs are present as such into the LNPs (Figure 2A).…”
Section: Discussionmentioning
confidence: 82%
“…Noble-metal nanoparticles (e.g., Au and Ag) have become increasingly important because of their unique features of localized surface Plasmon resonance, resulting in excellent activity and good sensitivity as SERS substrates [1,3,4,5]. However, using Au nanoparticles (AuNPs) or AgNPs colloids directly is often inconvenient in real-world applications due to the difficulties in handling fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocellulose can be used as a substrate for loading a range of different nanomaterials [18,19] and the resultant nanocomposites have merits from both of the individual nanomaterials. To date, SERS of AuNPs and AgNPs has been extensively studied [3,4,20,21]. The performance of AuNPs/nanocellulose or AgNPs/nanocellulose nanocomposites as SERS substrates has also been reported in several studies [22,23,24,25,26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%